Comparison of the Long-Term Efficacy of Targeting the Subthalamic Nucleus Versus the Globus Pallidus Interna for Deep Brain Stimulation Treatment of Motor Dysfunction in Patients With Parkinson’s Disease: A Meta-Analysis Study - Makenna Huhn; Matthew Prewett; Julien Rossignol; Gary L. Dunbar (Parkinson's Disease)
A cardinal symptom of Parkinson’s disease (PD) is motor dysfunction, including bradykinesia and tremors, which is quantified in the Unified PD Rating Scale (UPDRS). Although some medications provide palliative treatments for these motor deficits, their efficacy wanes and can produce unwanted side effects, such as dyskinesia. Deep-brain stimulation (DBS) has provided an alternative treatment strategy that can benefit many patients, but optimal target structures for DBS and its long-term efficacy are not fully understood. The present study represents a meta-analysis of the long-term (> 5 years) effects of DBS on the two most common targets, the subthalamic nucleus (STN) and the globus pallidus interna (GPi), on scores of motor performance using the UPDRS-III. The initial search of PubMed, Cochrane Library, and Clinical Trials resulted in 197 articles, of which 28 met the criteria for our analysis. Of the 1321 patients included, 1179 received STN DBS group and 142 received GPi DBS. UPDRS-III scores for both target groups were analyzed at baseline and at either 5–8 or 10–15 years later for both on- and off-medication phases. The results indicated that the STN stimulation is effective at reducing motor symptoms during off-medication treatment for up to 15 years and that the GPi stimulation can be effective for up to at least 8 years. Our findings further suggest that STN- and GPi-targeted DBS may wear off during the on-medication phase between 5 and 10 years of treatment. This study supports findings that both DBSs of either the STN or GPi have long-term efficacy, especially during off-medication periods.